TINGKAT PENGETAHUAN SISWA PUTRI SMA TENTANG KEHAMILAN USIA DINI DI DESA PANCASARI KECAMATAN SUKASADA KABUPATEN BULELENG BALI 2014 - Siti Umairah (E-Jurnal Medika Udayana, 2016)
THE KNOWLEDGE LEVEL OF SENIOR HIGH SCHOOL GIRLS ABOUT ADOLESCENT PREGNANCY AT PANCASARI VILLAGE SUKASADA SUBDISTRICT BULELENG REGENCY BALI 2014 Adolescent pregnancy is one of major health problems faced by developing country, including Indonesia. This phenomenon is related to knowledge and attitude of teenager towards adolescent pregnancy, this include sexual behavior. From January 2013 until October 2014 there are 25 pregnant women whose age is under 20 years old in Pancasari village. This study was designed to know the knowledge level of adolescent girls about adolescent pregnancy in Pancasari village, Buleleng regency. This study conducted using cross-sectional method. The sample was drawn using simple random sampling involving students at grade X, XI and XII at two senior high schools at Sukasada village. The data was collected from self-administered questionnaire filled by 150 respondents. The result showed that majority of respondent (52,7%; n=68) has sufficient knowledge regarding adolescent pregnancy, dominated by grade X, good (46,4%; n=26) and sufficient (48,5%; n=33). Most of the SMA students are categorized into sufficient knowledge of adolescent pregnancy.